Primary radiation therapy for advanced‐stage laryngeal cancer: A laryngo‐esophageal dysfunction disease‐free survival. Issue 6 (23rd November 2022) - Mohamad, Issa; Almousa, Abdelatif; Taqash, Ayat; Mayta, Ebrahim; Abuhijla, Fawzi; Ghatasheh, Hamza; Ababneh, Hazem; Wahbeh, Lina; Abuhijlih, Ramiz; Hussein, Tariq; Al‐Gargaz, Wisam; Hosni, Ali
Abstract: Objectives: To evaluate the outcomes of advanced‐stage laryngeal squamous cell carcinoma (SCC) patients treated with functional‐preservation strategy with a specific focus on laryngo‐esophageal dysfunction disease‐free survival (LEDDFS). Methods and materials: A retrospective review was conducted of stage III‐IVB laryngeal SCC patients who were treated with curative‐intent radiotherapy (RT) (2007–2018). Patients were preferentially managed with upfront chemoradiation (CCRT); except for those with cN2‐3, cT4, or large volume cT3 (induction chemotherapy followed by RT or CCRT is an option), and those who were unfit or declined chemotherapy (received altered RT). The primary endpoint was 3‐year LEDDFS, and secondary endpoints were 3‐year local failure (LF), regional failure (RF), distant metastasis (DM), overall survival (OS), disease‐free survival (DFS), and acute and late toxicities. Cox proportional hazard tests were used for multivariable analysis (MVA). Results: A total of 213 cases were included. With a median follow‐up of 37 months, the 3‐year LEDDFS was 50%, while the 3‐year OS, DFS, LF, RF, and DM were 81%, 74%, 9%, 5%, and 7%, respectively. On MVA, cT4‐category was the only predictor of inferior LEDDFS (HR: 0.47, [95% CI: 0.29–0.74], p < .01). The most common grade ≥ 3 acute and late radiation therapy oncology group (RTOG) toxicity were esophageal toxicity: 16.7% and 29.6%, respectively. Conclusions: Primary RT resulted in favorable oncologic and functional outcomes in only half of the advanced‐stage laryngeal cancer patients. Future clinical trials are required to investigate further treatment options aiming to improve the oncologic and maintain functional outcomes with utilization of LEDDFS as the primary endpoint. Level of evidence: 4. Abstract : A functional‐preservation strategy is a crucial approach in the management of stage III‐IVb laryngeal cancer. After intensified treatment, majority of the patients developed laryngeal dysfunction. T4 patients have a poor prognosis.